3D printing as a part of Finnish practical nurse students’ technological acceptance – a qualitative study - Alhonkoski, Mika; Gustafsson, Marja-Liisa; Ojanen, Kalle; Piili, Heidi; Salminen, Leena (Finnish Journal of eHealth and eWelfare, 2024)
3D printing is a solid part of the health care environment, and in the future, it could assume a more innovative role in the work carried out by practical nurses. However, the educational context may not support the preparedness to face and adapt new and creative technologies on the part of practical nursing students. This study aimed to describe practical nursing students’ technological acceptance towards 3D printing before and after six hours of 3D printing instruction. The technological acceptance model was used as a framework of the study. The data was collected using focus group interviews that 14 practical nursing students participated in before and after their six-hour 3D teaching course. Along with the thematic analysis, the interview themes were created in accordance with the theoretical elements concerned. The results showed four narrative themes that described how a six-hour lesson series changed the students’ technological acceptance towards 3D printing, from: 1) professional meaningless to everyday usefulness, 2) resource dominance to a part of working life, 3) special competence to ease of use, and 4) assumptions to limitless possibilities. Every theme consisted of two subthemes. Despite having been a new thing for students, 3D printing could be conceived in terms of having professional significance. The students described 3D printing as being easy to adapt to and they highlighted the meaning of its educational usage, as it could prepare them to be better with respect to applying creative working life-based technological solutions. As a conclusion, it can be stated that even short educational sessions can promote practical nursing students’ technological acceptance towards 3D technology and the know-how to implement it in working life. This requires educational institutions to target resources to 3D printing and on teacher education.